ADVENTURE FORMULA STORYLINE IN MAD MAX: FURY ROAD (2015) MOVIE DIRECTED BY GEORGE MILLER - Nuraini, Sri; Sudarisman, Yoga; Hkikmat, Mahi M (Saksama: Jurnal Sastra, 2024)
This research attempts to examine the adventure aspect that focuses on the storyline in the popular movie "Mad Max: Fury Road" directed by George Miller, released in 2015. The film shows a hero successfully completing a dangerous mission with fairly short but effective dialog to convey the intended message while advancing the story. Therefore, the researcher poses an analysis question which is how the adventure storyline is built in the movie of Mad Max: Fury Road (2015). To achieve the outcome of the question, this research identifies the adventure aspects that build the story by using the main formula theory by Sarick (2009). The method used in this research is qualitative method. The researcher uses dialog and character scenes as data to get results. From the results of the study, the researcher found 3 data which are the boundaries between the beginning of the movie, the middle of the movie, and the end of the storyline of the movie. The conclusion of the movie Mad Max: Fury Road can be understood that the adventure plot is very simple but gives a tense impression and although various obstacles are encountered during the travel process, the adventure narrative includes the ability to successfully survive and overcome dangerous circumstances involving physical, human, and animal risks, as well as the need to escape and pass through dangerous predicaments.